Mengintegrasikan Peran Ekosistem Dengan Hak Atas Lingkungan Yang Sehat - Yana Suryana; Edi Sutikno; Ramli Umar; Syarifuddin Nanti (Muhammadiyah Law Review Journal, 2026)
This study examines the integration of ecosystem protection with the right to a healthy environment as an essential component of human rights protection in addressing flood disasters in Indonesia. The study is motivated by the increasing frequency of floods caused not only by climate change but also by deforestation, land degradation, and weak spatial planning policies, which threaten fundamental human rights. This research employs a normative legal method using statutory, conceptual, and human rights approaches by analyzing the 1945 Constitution of the Republic of Indonesia, environmental and disaster management legislation, and relevant international human rights instruments. The findings reveal that ecosystem degradation has significantly increased disaster risks and undermined the rights to life, security, health, housing, and a healthy environment. Consequently, the State bears constitutional obligations to protect, respect, and fulfil these rights through ecosystem-based disaster mitigation, effective environmental law enforcement, protection of vulnerable groups, and comprehensive post-disaster recovery. The study concludes that integrating ecosystem conservation with the protection of environmental rights is essential to strengthening sustainable development, disaster resilience, and the realization of constitutional human rights in Indonesia.